La represión militar en la Argentina (1955-1976) - Pontoriero, Esteban Damián (Entre los libros de la buena memoria, 2022)
The military repression in Argentina (1955-1976). This book deals with the political repression carried out by the military regime in Argentina between 1955 and 1976. The author studies the defense policies of the constitutional and de facto governments, and the counterinsurgency approach, that is, the actions related to the Army's internal war. He also explores the transformation of the local sphere into the alleged battlefield of the so-called war against subversion, in which the Armed Forces had to intervene to repress and exterminate the internal enemy. The work focuses on a group of laws of exception, as well as on a series of theoretical and practical principles of Army doctrine, considering their implications for the making of a history of military repression.